Assessing Spatio‐Temporal Variability of Free Gas in Surficial Cohesive Sediments Using Tidal Pressure Fluctuations. Issue 10 (24th October 2021) - Garziglia, Sebastien; Sultan, Nabil; Thomas, Yannick; Ker, Stephan; Marsset, Bruno; Bompais, Xavier; Woerther, Patrice; Witt, Christoph; Kopf, Achim; Apprioual, Ronan
Abstract: From a geohazard assessment perspective, the distribution, content, and dynamics of free gas in surficial sediment were addressed by imaging and monitoring the upper 15 m beneath the shelf offshore Nice, France. Based on high‐resolution seismic data covering three sites where pore pressure was recorded over three and a half years, the presence of free gas was determined in the upper 2.75–14.75 m of cohesive, silty clay. Seismic velocity changes delineate two layers with gas volume fractions ranging from 0.12% to 1.89%. By considering the tidal response recorded by eight pore pressure sensors, estimates of gas volume fractions vary from 0.26% to more than 9.4% on a spatio‐temporal scale which cannot be achieved with seismic data. To depict spatio‐temporal patterns three types of free gas occurrence (FGO) were distinguished. Type 3 FGO uniquely showed sawtooth fluctuations in overpressure of 27%–45% of the hydrostatic effective stress as evidence of bubble growth and rise. The other two types showed long‐term overpressure trends indicative of a situation whereby bubble growth has ceased. Type 1 FGOs are distinguished from type 2 by their gas volume fraction lower than 9.4% and ratios of overpressure to hydrostatic effective stress lower than 0.3. Values higher than this threshold are considered sufficient for shear failure to initiate from the steep shelf edge (>20°). Beyond site‐specific insights, the distinction of FGO from their overpressure levels yields testable implications for the dynamics of methane in sediments. Plain Language Summary: Increased awareness of the role of gas bubbles in surficial sediments with regard to the stability of submarine slopes has stressed the need to quantify their distribution, content, and evolution with time. This was addressed by imaging and recording pressure fluctuations of shallow subsurface marine sediments. Both methods agreed in delineating the broad distribution of gas in these clayey deposits. However, they provided contrasting estimates of gas content which could be related to their distinct sensitivity to local changes. The analysis of the results obtained from the pressure records led to the recognition of three types of gas accumulations which cannot be discerned by imaging the subsurface. One type distinguishes from the others by showing episodic fluctuations in gas content and pressure ascribed to the growth and rise of bubbles. The other two types show trends in pressure suggesting that bubble growth has ceased. Of these two types, the one which is characterized by the highest gas content and pressure level is also considered to have the potential to initiate local shear failure in sediment. On a broader perspective, field evidences reported in this study provide constraints and testable implications for models addressing the transfer of methane to the atmosphere. Key Points: The inversion of seismic and long‐term pore pressure data indicates the presence of free gas in cohesive shelf sediments Three types of free gas occurrences are distinguished based on the estimated content of bubbles and monitored overpressure patterns The highest gas contents are found locally at the steep shelf edge where overpressures are sufficient to initiate shear failure